Development of radiodetection systems towards miniaturised quality control of PET and SPECT radiopharmaceuticals. Issue 9 (5th April 2016) - Taggart, Matthew P.; Tarn, Mark D.; Esfahani, Mohammad M. N.; Schofield, Daniel M.; Brown, Nathaniel J.; Archibald, Stephen J.; Deakin, Tom; Pamme, Nicole; Thompson, Lee F.
Abstract : Miniaturised silicon photomultipliers (SiPMs) were employed for the detection of radioactivity, towards the microfluidic quality control testing of radiopharmaceuticals. Abstract : The ability to detect radiation in microfluidic devices is important for the on-chip analysis of radiopharmaceuticals, but previously reported systems have largely suffered from various limitations including cost, complexity of fabrication, and insufficient sensitivity and/or speed. Here, we present the use of sensitive, low cost, small-sized, commercially available silicon photomultipliers (SiPMs) for the detection of radioactivity inside microfluidic channels fabricated from a range of conventional microfluidic chip substrates. We demonstrate the effects of chip material and thickness on the detection of the positron-emitting isotope, [ 18 F]fluoride, and find that, while the SiPMs are light sensors, they are able to detect radiation even through opaque chip materials via direct positron and gamma (γ) ray interaction. Finally, we employed the SiPM platform for analysis of the PET (positron emission tomography) radiotracers 2-[ 18 F]fluoro-2-deoxy-d -glucose ([ 18 F]FDG) and [ 68 Ga]gallium-citrate, and highlight the ability to detect the γ ray emitting SPECT (single photon emission computed tomography) radiotracer, [ 99m Tc]pertechnetate.